Comparative study of the influence of active groups of chitosan derivatives on antifungal activity. Issue 4 (15th May 2012) - Guo, Zhanyong; Ren, Jianming; Dong, Fang; Wang, Gang; Li, Pengcheng
Abstract: In this study, series of chitosan derivatives containing active groups were synthesized and evaluated for their antifungal activity against three crop‐threatening fungi, Fusarium oxysporum. f. sp. Vasinfectum, Alternaria solani, and Valsa mali . Schiff bases of carboxymethyl chitosan (As: 2‐(2‐hydroxy‐5‐nitrobenzylideneamino)‐6‐carboxymethyl chitosan; Bs: 2‐(2‐hydroxyl‐5‐chlorobenzaldimino)‐6‐carboxymethyl chitosan), N ‐substituted carboxymethyl chitosan (An: 2‐(2‐hydroxyl‐5‐nitrobenzylamino)‐6‐carboxymethyl chitosan; Bn: 2‐(2‐hydroxyl‐5‐chlorobenzylamino)‐6‐carboxymethyl chitosan) and 2‐urea‐carboxymethyl chitosan (Au: 2‐(2‐nitrophenylurea)‐6‐carboxymethyl chitosan; Bu: 2‐(2‐chlorophenylurea)‐6‐carboxymethyl chitosan) were synthesized, and their antifungal activity was comparatively studied by hypha measurement in vitro, respectively. Results obtained from this study revealed that the active groups combined with Schiff bases functional groups (CN) could strengthen the antifungal activity most effectively among the compounds studied in this work. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :